2015
DOI: 10.1177/0735633115620197
|View full text |Cite
|
Sign up to set email alerts
|

OpenSim-Supported Virtual Learning Environment

Abstract: The pedagogical and design considerations for the use of a virtual reality (VR) learning environment are important for prospective and current teachers. However, empirical research investigating how preservice teachers interact with transformative content representation, facilitation, and learning activities in a VR educational simulation is still limited. The purpose of this study is to examine prospective teachers' user experiences in a VR-based learning environment, thus exploring VR-based instructional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…The ability to create various environments has made 3D virtual worlds useful for experiencing dangerous or logistically impractical science labs, simulations, and medical experiments, which online students would have great difficulty seeing and experiencing in person (Koglbauer, 2015;Urso & Fisher, 2015). Virtual worlds have also been used to provide virtual tours of real geographic landforms to students of various ages (Argles et al, 2015;Kim & Ke, 2016). The ability to design complex environments makes virtual spaces ideal for providing experiential, constructivist learning experiences (Kluge & Riley, 2008).…”
Section: Why 3d Virtual Environments?mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to create various environments has made 3D virtual worlds useful for experiencing dangerous or logistically impractical science labs, simulations, and medical experiments, which online students would have great difficulty seeing and experiencing in person (Koglbauer, 2015;Urso & Fisher, 2015). Virtual worlds have also been used to provide virtual tours of real geographic landforms to students of various ages (Argles et al, 2015;Kim & Ke, 2016). The ability to design complex environments makes virtual spaces ideal for providing experiential, constructivist learning experiences (Kluge & Riley, 2008).…”
Section: Why 3d Virtual Environments?mentioning
confidence: 99%
“…They also appreciated the verbal and nonverbal flexibility of communication available. An exploratory study of preservice teachers experienced in a virtual simulation platform found that the participants appreciated the collaborative nature of the experience while also noting that an emphasis on explanatory communication before the experience and feedback during the simulation is necessary to enhance the virtual simulation experience (Kim & Ke, 2016). Thus, similar to Zeichner and Zilka’s (2016) findings, frequent communication was found to be essential to ensuring positive perceptions.…”
Section: Perceptions Of Virtual Environmentsmentioning
confidence: 99%
“…The use of computers in VLab has a positive impact in the form of games [5], simulators [6], [7], [8], and virtual machines (VM) [2], [9]. Many researchers suggested that teachers [10] and preservice teachers [11], [12], [13] design learning by involving VLab for education [14] starting from educational materials, learning activities, and contents to formulate evaluations [12].…”
Section: Virtual Laboratory For Education (Vle)mentioning
confidence: 99%
“…Otro grupo de investigaciones han obtenido como resultado el que su utilización favorece el desarrollo de la inteligencia espacial, la orientación espacial, las habilidades espaciales de la persona y la comprensión visual de los objetos y contextos. Estos resultados se han presentado tanto cuando los alumnos interaccionan con objetos de RA (Alvarez et al, 2017;Carbonnel y Bermejo, 2017; Del Cerro Velázquez y Morales-Méndez, 2017; Lee, Chen y Chang, 2016) como con los de RV (Guo, 2016;Hwang y Hu, 2013;Kim y Ke, 2016).…”
Section: Conclusiónunclassified